PENGARUH BAURAN PEMASARAN TERHADAP KEPUASAN PENGUNJUNG TAMAN SAFARI INDONESIA II PRIGEN PASURUAN JAWA TIMUR - Izky Dwi Ristanti; Arif Kuswanto (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2022)
This study was carried out to decide the impact of the marketing mix on the satisfaction of visitors to Taman Safari Indonesia II Prigen. While this research has the aim of understanding and analyzing how the marketing mix is offered to visitors, how the level of visitor satisfaction in the marketing mix, the magnitude of the influence of the marketing mix simultaneously and partially on the satisfaction of visitors at Taman Safari Indonesia II Prigen. The technique used on this studies is quantitative with the form of studies used is descriptive and causal. Samples have been taken the usage of a non-opportunity sampling technique with purposive sampling with a complete of four hundred respondents. In studying the data, descriptive evaluation and multiple regression evaluation have been used. After testing the simultaneity hypothesis, it is located that the first-rate of carrier has a big have an effect on at the delight of visitors at Taman Safari Indonesia II Prigen. From the consequences of partial speculation testing (t test) it changed into located that the variables iproduct, iprice, iplace, ipromotion, ipeople, iprocess, and physicali proof had a large have an impact on at the pride of traffic to Tamani Safari Indonesia II. Based at the coefficient of determination, it changed into located that the quantity of vacationer pleasure changed into 68.2% and the remaining 31.8% was caused by other factors not included in the research examined by researchers such as visiting decision factors and visitor loyalty